2013
DOI: 10.1016/j.jcrysgro.2013.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Growth of potassium tantalate (KTaO3) crystals by directional solidification

Abstract: crystallized when the ratio of K 2 CO 3 was more than 51.5 mol%. There were three kinds of color in the KTaO 3 -crystallized portions: milky white, colorless transparent and pale yellow. Based on these results, the phase diagram of the K 2 CO 3 -Ta 2 O 5 system around the stoichiometric composition of KTaO 3 is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Furthermore, KTaO 3 crystal boules have also been grown by directional solidification with a K 2 CO 3 −Ta 2 O 5 melt. 19 Sodium tantalate (NaTaO 3 ) has been recognized as a highly effective photocatalyst since Kato et al reported that La-doped NaTaO 3 loaded with NiO cocatalyst exhibited an apparent quantum yield of 56% and demonstrated high photocatalytic activity for water splitting. 20 Several methods have been used to synthesize NaTaO 3 particles, including solid-state synthesis, 21 hydrothermal synthesis, 22,23 sol−gel methods, 21,24 and flux methods.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, KTaO 3 crystal boules have also been grown by directional solidification with a K 2 CO 3 −Ta 2 O 5 melt. 19 Sodium tantalate (NaTaO 3 ) has been recognized as a highly effective photocatalyst since Kato et al reported that La-doped NaTaO 3 loaded with NiO cocatalyst exhibited an apparent quantum yield of 56% and demonstrated high photocatalytic activity for water splitting. 20 Several methods have been used to synthesize NaTaO 3 particles, including solid-state synthesis, 21 hydrothermal synthesis, 22,23 sol−gel methods, 21,24 and flux methods.…”
mentioning
confidence: 99%
“…These crystal substrates can reach up to 10 mm, whereas crystals grown by either flux or hydrothermal synthesis are less than 5 mm. Furthermore, KTaO 3 crystal boules have also been grown by directional solidification with a K 2 CO 3 –Ta 2 O 5 melt …”
mentioning
confidence: 99%
“…On the other hand, at lower temperatures, there is a tendency toward the formation of undesirable secondary phases, such as pyrochlore (K 2 Ta 2 O 6 ), which is detrimental for dielectric properties. [146][147][148] Several techniques, including solvothermal, [149][150][151] sol-gel, [152,153] directional solidification, [154] polymeric precursor-based reactions, [155] solid state reaction, [156,157] and hydrothermal methods [158,159] have been used with varying degrees of success to prepare KTO powder, single crystals and thin films. The conventional solidstate reaction involves the thorough mixing of stoichiometric amounts of K 2 O or K 2 CO 3 and Ta 2 O 5 , calcination and annealing at high temperatures for long periods.…”
Section: Polycrystalline Materials and Single Crystalsmentioning
confidence: 99%